Effect of the diet on performance characteristics and quality of meat fat of lamb by principal component analysis - Marcus Andrade Wanderley Junior; Cristiane Leal dos Santos; Leandro Pereira Lima; Thon Jovita Farias; Rodrigo Soares Junqueira; Ivon Pinheiro Lôbo; Jeferson Ladeia dos Santos; Andrezza Miguel da Silva (Acta Scientiarum. Animal Sciences, 2021)
The objective of this study was to evaluate the effect of use of agroindustrial co-products in the diet of lambs on the performance and nutritional quality of meat fat. Twenty lambs were distributed into four experimental groups: control diet (C) or diets containing cottonseed (CS), sunflower meal (SFM), and castor cake (CC). During the experimental period, data on dry matter consumption (DMC) and total weight gain (TWG) were collected. After slaughter, samples of Logissimus dorsi (LD) muscle were taken for fatty acids and cholesterol analysis. Diets C and CS provided similar characteristics of fat quality and animal performance. However, SFM and CC diets tend to form isolated groups, with different fat and performance characteristics. The SFM diet results in meat with a higher saturated fatty acids and cholesterol content. The CC diet is related to improved performance characteristics and lower cholesterol content. In conclusion, the inclusion of CC in the experimental diets provided, in the proportions used in this experiment, better characteristics of animal performance and meat fat quality.